Estudo das características morfoanatômicas, fitoquímicas e de atividade biológica de Passiflora malacophylla Mast. (Passifloraceae) - De Palma, Nicolás (2018)
Passiflora malacophylla Mast. (Passifloraceae) is a species native to Brazil that lacks anatomical studies and has few chemical and biological studies. In this sense, the present work had as objective the study of its morpho-anatomical and phytochemical characteristics, and the in vitro evaluation of the antioxidant and anticholinesterase activities. For this, vegetative aerial parts were collected and analyzed by means of stereoscopic microscopy, optical microscopy and scanning electron microscopy. The chemical study was carried out from crude methanolic extracts of both stem and leaves, which were partitioned with solvents of different polarities: hexane, chloroform and ethyl acetate. The crude extracts were analyzed by High Performance Liquid Chromatography, which allowed qualitative and quantitative differences between them to be observed. The fractionation of the extracts was done by means of Chromatography in Column which made possible the isolation of the phytosteroid daucosterol and the flavonoid vitexin. The antioxidant activity of the extracts was evaluated by the DPPH free radical sequestration assay. In this sense, were highlighted ethyl acetate extract of the stem (% SRL = 91.19±0.64, EC50 = 2.51 mg/mL) and ethyl acetate extract of the leaves (% SRL = 73.08±2.84 ; EC50 = 2.52 mg/mL). The anticholinesterase activity of the extracts was evaluated through the Ellman test, which allowed to conclude that these have low, moderate and potent inhibition of the acetylcholinesterase enzyme. The present study provides unpublished results on the anatomy of P. malacophylla, and also suggests that this species could be a promising source of biologically active substances.